Composite positive electrode sheet, battery, and electric device
Patent Information
- Application Number
- CN202610912120.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-13
AI Technical Summary
该反应不仅不可逆地消耗体系内的活性锂源,导致容量迅速衰减,同时破坏了负极界面的稳定性
[0004]本发明旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本发明提出一种复合正极片、电池和用电装置。
Smart Images

Figure CN122907580A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to composite cathode sheets, batteries, and electrical devices. Background Technology
[0002] With the increasing demand for high-energy-density lithium-ion batteries, high-nickel ternary cathode materials are widely used due to their high specific capacity. However, their application still faces several severe technical bottlenecks and safety hazards: First, under extreme conditions such as thermal abuse or overcharging, high-nickel cathode materials exhibit poor structural stability, easily leading to lattice collapse and the precipitation of active oxygen. The precipitated lattice oxygen reacts violently with the organic electrolyte and the active material on the negative electrode surface, rapidly releasing heat and potentially causing thermal runaway, even resulting in serious consequences such as combustion or explosion. Second, during cycling, the oxygen precipitated from the cathode migrates through the separator to the negative electrode side. When the negative electrode uses high-capacity silicon-based materials, the oxygen reacts with the lithium-intercalated silicon to generate electrochemically inert lithium oxide and silicon oxide. This reaction not only irreversibly consumes the active lithium source within the system, leading to rapid capacity decay, but also disrupts the stability of the negative electrode interface.
[0003] Therefore, the safety and stability issues caused by oxygen evolution at the positive electrode still need further improvement. Summary of the Invention
[0004] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention proposes a composite positive electrode, a battery, and an electrical device.
[0005] In a first aspect, this application provides a composite positive electrode sheet. According to an embodiment of this application, the composite positive electrode sheet includes: a positive current collector; a positive electrode material layer disposed on at least one side of the positive current collector; and an interface layer disposed on the side of the positive electrode material layer away from the current collector, comprising a polymer matrix and an oxygen scavenger, the oxygen scavenger being dispersed in the polymer matrix, the polymer matrix comprising a first polymer capable of absorbing electrolyte and swelling.
[0006] This composite cathode sheet can effectively suppress oxygen evolution in the cathode without sacrificing battery dynamic performance, improve the safety and stability issues caused by oxygen evolution, significantly enhance the cycle stability and safety of the cathode material, and at the same time enable the battery to have excellent rate performance.
[0007] According to an embodiment of this application, the oxygen scavenger is adsorbed onto the first polymer.
[0008] According to embodiments of this application, the first polymer has a strongly polar group, which includes at least one selected from cyano, carbonyl, ester, amide, etheroxy, hydroxy, carboxyl, sulfonyl, and phosphonate groups; the oxygen scavenger has a polar group, which includes at least one selected from sulfite, phosphite, hypophosphite, hydroxyl, silanol, carboxylate, metal-oxygen bond, and metal coordination site.
[0009] According to an embodiment of this application, the interface layer further includes an inorganic solid electrolyte, which is dispersed in the polymer matrix.
[0010] According to embodiments of this application, the composite positive electrode sheet satisfies at least one of the following conditions: The oxygen scavenger includes at least one of a chemically active oxygen scavenger and a physically adsorbed oxygen scavenger, preferably the chemically active oxygen scavenger. The inorganic solid electrolyte includes at least one of oxide solid electrolyte, halide solid electrolyte, and sulfide solid electrolyte; The first polymer comprises hydrogenated nitrile butadiene rubber.
[0011] According to embodiments of this application, the composite positive electrode sheet satisfies at least one of the following conditions: The chemically active deoxidizing agent includes at least one of sulfite, phosphite, and hypophosphite; The physical adsorption type oxygen scavenger includes at least one of zeolite molecular sieve, metal-organic framework material, and porous silica. The oxide solid electrolyte includes at least one of garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte, and LISICON-type solid electrolyte; The halide solid electrolyte includes Li3YCl6; The sulfide solid electrolyte includes a sulfide-germanium ore type solid electrolyte, preferably including at least one of Li6PS5X and LGPS type solid electrolytes, wherein X is selected from Cl, Br and I; The acrylonitrile content of the hydrogenated nitrile rubber is >30%; The degree of hydrogenation of the hydrogenated nitrile butadiene rubber is <98%, preferably 90% < the degree of hydrogenation of the hydrogenated nitrile butadiene rubber <98%.
[0012] According to embodiments of this application, the polymer matrix further includes a second polymer that does not swell in the electrolyte; wherein the second polymer comprises a matrix polymer, or the second polymer comprises a matrix polymer and a reinforcing phase.
[0013] According to embodiments of this application, the composite positive electrode sheet satisfies at least one of the following conditions: The matrix polymer includes fluorinated polymers, preferably including at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluorochloroethylene copolymer, polytetrafluoroethylene, and ethylene-tetrafluoroethylene copolymer; The reinforcing phase is dispersed in the matrix polymer, or the reinforcing phase is composite with the matrix polymer; The shape of the reinforcing phase includes at least one of microparticles and fibers; The reinforcing phase includes at least one of polyimide and polyamide-imide; Based on the total mass of the second polymer, the mass percentage of the reinforcing phase is 1wt%-30wt%, preferably 5wt%-20wt%; The mass ratio of the first polymer to the second polymer is 20:80 to 80:20, preferably 30:70 to 70:30.
[0014] According to embodiments of this application, the composite positive electrode sheet satisfies at least one of the following conditions: The thickness of the interface layer is 0.5μm to 5μm; Based on the total mass of the interface layer, the polymer matrix has a mass percentage content of 10-70 wt%, preferably 20-50 wt%. Based on the total mass of the interface layer, the oxygen scavenger has a mass percentage content of 5-35 wt%, preferably 10-25 wt%. Based on the total mass of the interface layer, the mass percentage of the inorganic solid electrolyte is 10-80 wt%, preferably 30-60 wt%.
[0015] According to embodiments of this application, the interface layer further includes an auxiliary agent, and the auxiliary agent satisfies at least one of the following conditions: The additives include at least one of dispersants, rheology modifiers, and conductive agents; Based on the total mass of the interface layer, the mass percentage of the additive does not exceed 10 wt%.
[0016] According to an embodiment of this application, the cathode material layer includes a medium-high nickel ternary cathode material, wherein the percentage of nickel element in the total molar amount of transition metal elements in the medium-high nickel ternary cathode material is not less than 60%.
[0017] A second aspect of this application provides a battery. According to an embodiment of this application, the battery includes a positive electrode, a negative electrode, a gel-state interface layer, and an electrolyte. The gel-state interface layer is disposed between adjacent positive and negative electrode sheets, and is formed by the interface layer absorbing and swelling the electrolyte, as defined above. In this battery, the gel-state interface layer can effectively capture oxygen released from the positive electrode, thereby significantly improving the cycle stability and safety of the medium-high nickel positive electrode material, while ensuring excellent rate performance of the cell.
[0018] A third aspect of this application provides an electrical device. According to embodiments of this application, the electrical device includes the composite positive electrode or the battery described above. This electrical device possesses all the features and advantages of the composite positive electrode or battery described above, which will not be elaborated upon here. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the structure of a composite positive electrode sheet according to an embodiment of this application.
[0020] Figure 2 This is a three-dimensional structural schematic diagram of a composite positive electrode sheet according to an embodiment of this application.
[0021] Figure 3 This is a schematic diagram of the structure of a battery according to an embodiment of this application.
[0022] Figure 4 This is a three-dimensional structural diagram of a battery according to an embodiment of this application.
[0023] Figure label: 10: Positive current collector; 20: Positive electrode material layer; 30: Interface layer; 31: Gel-state interface layer; 40: Separator; 50: Negative electrode material layer; 60: Negative current collector; 100: Positive electrode sheet; 200: Negative electrode sheet. Detailed Implementation
[0024] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0025] In a first aspect, this application provides a composite positive electrode. According to an embodiment of this application, referring to... Figure 1The composite positive electrode sheet includes: a positive current collector 10; a positive electrode material layer 20 disposed on at least one side of the positive current collector 10; and an interface layer 30 disposed on the side of the positive electrode material layer 20 away from the current collector 10. The interface layer 30 includes a polymer matrix and an oxygen scavenger, the oxygen scavenger being dispersed in the polymer matrix. The polymer matrix includes a first polymer that can absorb electrolyte and swell. This composite positive electrode sheet, used in batteries, can effectively suppress positive electrode oxygen evolution without sacrificing battery kinetic performance, improve the safety and stability issues caused by positive electrode oxygen evolution, significantly enhance the cycle stability and safety of the positive electrode material, and simultaneously enable the battery to have excellent rate performance.
[0026] Specifically, the oxygen scavenger in the aforementioned interface layer possesses strong oxygen-capturing capabilities, effectively capturing oxygen evolved from the positive electrode and removing it before it diffuses to the negative electrode or reacts with the electrolyte, fundamentally blocking the chain reaction initiated by oxygen. Furthermore, when used in a battery, the first polymer within the interface layer absorbs the electrolyte and swells, forming a gel state. The three-dimensional gel network of the first polymer is filled with liquid electrolyte, creating highly efficient lithium-ion transport channels with minimal hindrance to lithium-ion migration, thus ensuring battery performance under high-rate charge-discharge conditions. Additionally, this interface layer can be prepared in situ, exhibiting good compatibility with existing battery processes.
[0027] According to embodiments of this application, the oxygen scavenger is adsorbed onto the first polymer. This allows the oxygen scavenger to be more uniformly dispersed in the interfacial layer, less prone to aggregation, and less likely to migrate after swelling from absorbing the electrolyte.
[0028] According to embodiments of this application, the first polymer has a strongly polar group, and the oxygen scavenger has a polar group or polar site. The oxygen scavenger and the first polymer can be physically adsorbed through the polar group or polar site on the oxygen scavenger and the strongly polar group on the first polymer. In some embodiments, the strongly polar group includes at least one selected from cyano, carbonyl, ester, amide, etheroxy, hydroxy, carboxyl, sulfonyl, and phosphonate groups; the polar group includes at least one selected from sulfite, phosphite, hypophosphite, hydroxyl, silanol, carboxylate, metal-oxygen bond, and metal coordination site. Therefore, the oxygen scavenger can be more uniformly dispersed on the first polymer, less prone to aggregation and migration, thus better exerting its oxygen supplementation effect.
[0029] According to embodiments of this application, the oxygen scavenger includes at least one of a chemically active oxygen absorber and a physically adsorbed oxygen scavenger. The chemically active oxygen absorber utilizes the reducing property of anions to undergo a rapid and irreversible redox reaction with the active oxygen released from the positive electrode, achieving irreversible removal of oxygen. Simultaneously, it can neutralize or buffer acidic byproducts (such as HF) generated from electrolyte decomposition in situ, thereby inhibiting interfacial corrosion. The physically adsorbed oxygen scavenger can physically adsorb and fix the evolved oxygen, thereby reducing the diffusion rate of oxygen within the battery cell and delaying its migration to the negative electrode side.
[0030] It is understood that chemically active oxygen absorbers can achieve irreversible removal of oxygen and are more advantageous in suppressing oxygen participation in side reactions under conditions such as thermal abuse and overcharging. Physically adsorbed oxygen absorbers, on the other hand, focus more on adsorbing, buffering, and blocking the diffusion of trace gases during the cycle. Considering that the adsorption-desorption equilibrium may change under high-temperature conditions, physically adsorbed oxygen absorbers are preferred as a supplement to improve oxygen fixation efficiency and reduce the risk of oxygen diffusion. Therefore, this application prefers chemically active oxygen absorbers.
[0031] According to embodiments of this application, the chemically active oxygen absorber includes at least one of sulfite, phosphite, and hypophosphite; in some embodiments, the chemically active oxygen absorber can be micron- or nano-sized sulfite, phosphite, or hypophosphite. These types of chemically active oxygen absorbers have stronger oxygen replenishment and capture capabilities, and the materials are widely available. Furthermore, micron- or nano-sized oxygen absorbers can further increase the specific surface area of the oxygen absorber, resulting in a larger contact area with the oxygen evolved at the positive electrode, thereby further improving the oxygen capture efficiency.
[0032] In this article, micrometer or nanometer scale refers to the particle size of the oxygen scavenger being in the micrometer or nanometer range. The particle size of the oxygen scavenger can be determined by measuring its median particle size distribution (D50) using a laser particle size analyzer; alternatively, for nanoscale particles, the material morphology can be directly observed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM) and then detected using image analysis software methods.
[0033] According to embodiments of this application, the physically adsorbed oxygen scavenger is an inorganic material with a high specific surface area and a certain microporous structure. Specifically, the physically adsorbed oxygen scavenger includes at least one of zeolite molecular sieves, metal-organic framework materials, and porous silica. These materials have abundant porous structures, which can better adsorb oxygen evolved at the positive electrode, and the adsorption capacity is high.
[0034] According to embodiments of this application, the interface layer further includes an inorganic solid electrolyte dispersed in the polymer matrix. By introducing an inorganic solid electrolyte into the interface layer, inorganic ion conduction channels can be constructed, which, together with the gel phase formed in situ after liquid injection, form an organic-inorganic composite transport path, thereby solving the problem that all-solid-state dense membranes cannot adapt to ion transport in liquid / gel phase electrolytes.
[0035] According to embodiments of this application, the inorganic solid electrolyte can be selected from those with high ionic conductivity and electrochemical stability. In some embodiments, the inorganic solid electrolyte includes at least one of oxide solid electrolytes, halide solid electrolytes, and sulfide solid electrolytes.
[0036] Specifically, the oxide solid electrolyte includes at least one of garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte, and LISICON-type solid electrolyte; the halide solid electrolyte includes Li3YCl6; and the sulfide solid electrolyte includes silver sulfide germanite-type solid electrolyte, specifically including at least one of Li6PS5X and LGPS-type solid electrolyte, wherein X is selected from Cl, Br, and I. The above-mentioned inorganic solid electrolytes can construct better inorganic lithium-ion conduction channels, which is more conducive to reducing interfacial impedance and improving rate performance.
[0037] According to embodiments of this application, the first polymer comprises hydrogenated nitrile butadiene rubber. The strongly polar cyano groups (-CN) therein enhance the polar interfacial interaction between the polymer substrate and the oxygen scavenger, promoting uniform dispersion and stable fixation of the oxygen scavenger in the interfacial layer. It also improves the affinity and wettability of the polymer substrate to the electrolyte, particularly for polar carbonate electrolytes, which is a crucial foundation for achieving post-filling liquid absorption, swelling, gelation, and the construction of liquid-phase ion transport channels. Furthermore, after battery filling, the first polymer can form a liquid-containing gel microenvironment in situ, facilitating oxygen mass transfer and deoxygenation reactions at the interface and reducing the risk of migration or secondary aggregation of the oxygen scavenger in the swollen state.
[0038] According to embodiments of this application, the hydrogenated nitrile rubber has an acrylonitrile content >30%. A higher acrylonitrile content means that the molecular chain contains a higher density of strongly polar cyano groups (-CN), which can further enhance the polar interfacial interaction between the polymer substrate and the oxygen scavenger, further promote the uniform dispersion and stable fixation of particles in the coating, and further improve the affinity and wettability of the polymer substrate to the electrolyte. If the acrylonitrile content is too low (e.g., <30%), the polymer polarity may be insufficient, which may lead to poor dispersion stability of the oxygen scavenger in the interfacial layer, making it prone to aggregation, thereby reducing the effective interfacial interface; and reducing the wetting and swelling capacity of the interfacial layer to the electrolyte, resulting in insufficient gelation, which may hinder interfacial ion transport and increase interfacial impedance.
[0039] In this article, the acrylonitrile content of hydrogenated nitrile butadiene rubber refers to the mass percentage of acrylonitrile monomer structural units bonded in its molecular chain. It can be tested by elemental analysis (using the Kjeldahl nitrogen determination method or the Dumas combustion method to determine the total nitrogen content of the polymer and calculate it accordingly) or Fourier transform infrared spectroscopy (FTIR).
[0040] According to embodiments of this application, the degree of hydrogenation of the hydrogenated nitrile rubber is <98%, specifically 90% < degree of hydrogenation of the hydrogenated nitrile rubber <98%. This achieves a better balance between oxidation resistance and swelling / ion transport. Specifically, controlling the degree of hydrogenation to <98%, i.e., retaining trace amounts of residual unsaturated structures, helps avoid excessive regularization of molecular chain segments, allowing the first polymer to maintain more suitable chain segment movement and swelling behavior in the electrolyte environment. This facilitates the electrolyte's entry into the first polymer network and the formation of low-resistance liquid-containing gel channels. Simultaneously, a higher degree of hydrogenation also improves the oxidation resistance of the first polymer under high-voltage positive electrode / reactive oxygen environments. If the hydrogenation is too high (e.g., ≥98%), the chain segment regularity and modulus may be too high, limiting the electrolyte's penetration or swelling of the first polymer, hindering the formation of ion transport channels, and potentially affecting rate capability and low-temperature performance. If the hydrogenation is too low, excessive residual unsaturated structures make it more prone to oxidative aging and decomposition reactions, leading to decreased interfacial layer stability.
[0041] In this article, the degree of hydrogenation of hydrogenated nitrile rubber refers to the percentage of hydrogen-saturated butadiene structural units in its molecular chain relative to the total number of butadiene structural units before and after hydrogenation (i.e., the degree of double bond saturation), which can be tested by nuclear magnetic resonance hydrogen spectroscopy or Fourier transform infrared spectroscopy (FTIR).
[0042] According to embodiments of this application, the polymer matrix further includes a second polymer that does not swell in the electrolyte. Thus, the second polymer can serve as a three-dimensional support framework to maintain the interfacial layer structure and stability, and to constrain and support the deformation of the first polymer network during swelling, thereby preventing interfacial layer instability from adversely affecting ion transport. Simultaneously, the synergistic effect of the elasticity of the first polymer and the rigidity of the second polymer can provide an in-situ buffer against particle volume changes caused by oxidation products (such as sulfates / phosphates) formed after oxygen capture by the oxygen scavenger, thereby improving the structural integrity and chemical stability of the interfacial layer during long-term cycling.
[0043] According to embodiments of this application, the second polymer may include a matrix polymer; specifically, the second polymer may be composed of a matrix polymer.
[0044] According to embodiments of this application, the matrix polymer includes a fluorinated polymer, specifically including at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), polytetrafluoroethylene (PTFE), and ethylene-tetrafluoroethylene copolymer (ETFE). The aforementioned second polymer provides better support performance, further enhancing the structure and stability of the interface layer, and further improving the structural integrity and chemical stability of the interface layer during long-term cycling.
[0045] According to embodiments of this application, the second polymer comprises a matrix polymer and a reinforcing phase. The reinforcing phase may be dispersed in the matrix polymer, or it may be composited with the matrix polymer. This improves the structural strength and interfacial stability of the interface layer.
[0046] According to embodiments of this application, the shape of the reinforcing phase includes at least one of microparticles and fibers. This allows for better reinforcement and facilitates dispersion.
[0047] According to embodiments of this application, the reinforcing phase includes at least one of polyimide (PI) and polyamide-imide (PAI). This results in superior strength and superior high-pressure resistance.
[0048] As an example, the matrix polymer in the second polymer can be PVDF and / or PVDF-HFP, or a composite system with PVDF or PVDF-HFP as the continuous phase and PI or PAI as reinforcing phases. Thus, the second polymer can further improve the stability of the interface layer.
[0049] According to embodiments of this application, based on the total mass of the second polymer, the mass percentage content of the reinforcing phase is 1wt%-30wt%, preferably 5wt%-20wt%, specifically such as 1wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, or any range between two of these. Within the above content range, the reinforcing phase (such as PI, PAI) can construct a coherent three-dimensional microskeleton with high mechanical strength in the matrix polymer, effectively suppressing structural collapse or excessive deformation of the interface layer under long-term cycling and electrolyte wetting, thereby significantly improving the mechanical stability and high-voltage resistance of the interface layer. If the content of the reinforcing phase is too low (e.g., below 1 wt%), it may be difficult to form an effective three-dimensional support network. This can lead to dimensional deformation, slippage, or even cracking of the interfacial layer when the first polymer absorbs liquid and swells, thus failing to maintain the structural stability of the interfacial layer. If the content of the reinforcing phase is too high, the high rigidity of the reinforcing phase can reduce the overall flexibility and increase the brittleness of the interfacial layer. This can easily lead to microcracks or coating peeling during electrode rolling or battery charge / discharge volume breathing. Furthermore, excessive rigid insulating skeletons increase the tortuosity of lithium-ion transport, hindering effective electrolyte penetration and significantly increasing the ion transport impedance at the interface, thus deteriorating the battery's rate performance and low-temperature kinetic performance.
[0050] According to embodiments of this application, the mass ratio of the first polymer to the second polymer is 20:80 to 80:20, specifically 30:70 to 70:30, such as 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, or any range between two of these. This ratio range allows the interface layer to have a suitable swelling ratio when used in a battery, forming a sufficiently gelled microenvironment, which is beneficial for forming good liquid-phase ion transport channels, while also maintaining good dimensional stability. If the proportion of the first polymer is too high, the swelling ratio of the interface layer may be too large, reducing dimensional stability and making slippage more likely; if the proportion of the first polymer is too low, the liquid absorption capacity of the interface layer may be insufficient, making it difficult to form a sufficiently gelled microenvironment, resulting in limited liquid-phase ion transport channels.
[0051] According to embodiments of this application, based on the total mass of the interface layer, the mass percentage content of the polymer matrix is 10-70 wt%, specifically 20-50 wt%. As an example, based on the total mass of the interface layer, the mass percentage content of the polymer matrix can specifically be 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, or any range between two of these.
[0052] According to embodiments of this application, based on the total mass of the interface layer, the mass percentage content of the oxygen scavenger is 5-35 wt%, specifically 10-25 wt%. As an example, based on the total mass of the interface layer, the mass percentage content of the oxygen scavenger can specifically be 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, or any range between two of these.
[0053] According to embodiments of this application, based on the total mass of the interface layer, the mass percentage of the inorganic solid electrolyte is 10-80 wt%, specifically 30-60 wt%. As an example, based on the total mass of the interface layer, the mass percentage of the inorganic solid electrolyte can specifically be 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, or any range between two of these.
[0054] The aforementioned ratio range allows the interface layer to possess both excellent oxygen removal and ion conduction capabilities, maintaining low ion transport impedance while exhibiting continuous oxygen capture and superior cycling stability. If the oxygen scavenger content is too low, it will be difficult to effectively suppress oxygen diffusion and side reactions during long cycles; if the oxygen scavenger content is too high, the content of electronic and ion insulating particles may be excessive, leading to interface layer embrittlement, and the accumulation of captured products may cause uncontrolled volume expansion, increasing ion transport resistance. If the polymer substrate content is too low, film formation may be difficult, the interface layer may easily crack / powder, and interface stability may be poor; if the polymer substrate content is too high, the functional components may be diluted, reducing oxygen capture efficiency per unit area, and an excessively large polymer phase ratio may increase the ion migration barrier. If the solid electrolyte content is too high, the slurry solid content may be too high during preparation, leading to poor viscosity and coatability, decreased interface layer flexibility, and easy formation of microcracks or peeling from the electrode.
[0055] According to embodiments of this application, the interface layer further includes additives. This can further improve the overall performance of the interface layer.
[0056] In some embodiments, the additives include at least one of dispersants, rheology modifiers, and conductive agents.
[0057] In some embodiments, the mass percentage of the additive does not exceed 10 wt% based on the total mass of the interface layer.
[0058] According to embodiments of this application, the thickness of the interface layer is 0.5 μm to 5 μm, specifically within the range of 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or any two of these ranges. This thickness range provides good oxygen capture capability while minimizing other negative impacts on the battery.
[0059] According to embodiments of this application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0060] According to embodiments of this application, the positive electrode material layer may include a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent; suitable functional additives may also be added as needed, including but not limited to lithium supplements, sodium supplements, film-forming agents, flame retardants, etc.
[0061] According to embodiments of this application, the positive electrode active material may include ternary positive electrode materials. In some embodiments, the positive electrode active material includes medium-high nickel ternary positive electrode materials. Herein, medium-high nickel ternary positive electrode materials refer to ternary positive electrode materials with a nickel molar content (i.e., the molar content of nickel based on the total molar amount of transition metal elements in the ternary positive electrode material) of not less than 60%. Specifically, the safety risk of ternary positive electrode materials increases with increasing nickel content. By setting the interface layer of this application, oxygen released from the positive electrode can be effectively captured, thereby significantly improving the cycle stability and safety of medium-high nickel positive electrode materials, while ensuring excellent rate performance of the battery.
[0062] According to the embodiments of this application, the specific type of positive electrode binder is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA), and styrene-butadiene rubber (SBR).
[0063] According to embodiments of this application, the positive electrode conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0064] A second aspect of this application provides a battery. According to an embodiment of this application, referring to... Figure 2The battery includes a positive electrode 100, a negative electrode 200, a gel-state interface layer 31, and an electrolyte. The gel-state interface layer 31 is disposed between adjacent positive electrode 100 and negative electrode 200. The gel-state interface layer 31 is formed by the interface layer absorbing the electrolyte and swelling, as defined above. In this battery, the gel-state interface layer can effectively capture oxygen released from the positive electrode, thereby significantly improving the cycle stability and safety of the medium-high nickel positive electrode material. Simultaneously, the gel-state interface layer has excellent ion transport performance, enabling the battery to have excellent rate performance.
[0065] According to embodiments of this application, the gel-state interface layer can be disposed between the positive and negative electrode sheets, for example, between the positive electrode sheet and the separator, which can achieve the effects of blocking diffusion, absorbing / fixing oxygen, and suppressing side reactions. Specifically, it can be directly disposed on the surface of the positive electrode material layer (i.e., it can be provided in the form of a composite positive electrode sheet), thereby allowing processing closer to the oxygen evolution source.
[0066] As can be understood, the composition, ratio, and thickness of the interface layer are consistent with the previous description, and will not be repeated here. The first polymer in the interface layer can absorb the electrolyte and swell, thereby forming a gel-like interface layer.
[0067] According to an embodiment of this application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one side of the negative electrode current collector, the negative electrode material layer including a negative electrode active material.
[0068] According to embodiments of this application, the negative electrode current collector can be a metal foil or a composite current collector. For example, copper foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0069] According to embodiments of this application, the negative electrode active material may be any negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. Silicon-based materials may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide compounds, and tin alloys.
[0070] According to embodiments of this application, the negative electrode material layer may optionally include a negative electrode binder. The negative electrode binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0071] According to embodiments of this application, the negative electrode material layer may optionally include a negative electrode conductive agent. The negative electrode conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0072] According to embodiments of this application, the negative electrode material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0073] According to embodiments of this application, there are no particular limitations on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected. In some embodiments of this application, the material of the separator membrane may include at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The separator membrane may be single-layered or multi-layered.
[0074] According to embodiments of this application, the electrolyte includes an electrolyte salt and an organic solvent, wherein the specific types and components of the electrolyte salt and the organic solvent are not specifically limited and can be selected according to actual needs.
[0075] For example, the organic solvent can be at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). In specific embodiments, two or more of the above-mentioned organic solvents can be selected.
[0076] The electrolyte salt serves as the ion source and can be any electrolyte salt known in the art for use in battery electrolytes. Exemplarily, the electrolyte salt can be at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium nitrate (LiNO3), and lithium fluoride (LiF).
[0077] A third aspect of this application provides an electrical device. According to embodiments of this application, the electrical device includes the composite positive electrode or the battery described above. This electrical device possesses all the features and advantages of the composite positive electrode or battery described above, which will not be elaborated upon here.
[0078] Specifically, the aforementioned electrical equipment can include, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0079] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.
[0080] Example 1 Positive electrode preparation (including interface layer preparation): 1) Preparation of the bottom positive electrode sheet: The positive electrode active material is a high-nickel ternary LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2. N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred evenly in a vacuum mixer to obtain a positive electrode slurry with a solid content of 70%. The positive electrode slurry was uniformly coated on the surface of an aluminum foil current collector with a thickness of 12 μm, dried at 110℃, and then cold-pressed and slit to obtain the bottom positive electrode sheet.
[0081] 2) Interfacial Layer Preparation: The first polymer, hydrogenated nitrile butadiene rubber (HNBR, acrylonitrile content of 35%, hydrogenation degree of 95%), and the second polymer, polyvinylidene fluoride (PVDF), were dissolved in NMP solvent at a mass ratio of 6:4 to form a polymer matrix solution. Subsequently, the inorganic solid electrolyte LATP (Li... 1.3 Al 0.3 Ti 1.7(PO4)3 (median particle size Dv50 approximately 500 nm) and sodium sulfite (Na2SO3, median particle size Dv50 approximately 1 μm), a chemically active deoxidizer. The mass percentages of each component in the interface layer dry film were controlled as follows: chemically active deoxidizer 20 wt%, inorganic solid electrolyte 45 wt%, and polymer matrix 35 wt% (of which HNBR accounts for 21 wt% and PVDF accounts for 14 wt%). The mixture was uniformly dispersed by ultrasonication and high-speed shearing to form an interface layer slurry. This slurry was uniformly coated onto the surface of the aforementioned bottom positive electrode sheet and vacuum dried at 80°C to form an interface layer with a thickness of 2 μm, thus obtaining the composite positive electrode sheet of this embodiment.
[0082] Negative electrode preparation: Artificial graphite (the negative electrode active material) is mixed with silicon carbide, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC-Na), and binder styrene-butadiene rubber (SBR) in a certain mass ratio. Deionized water is added as a solvent, and the mixture is stirred evenly to obtain a negative electrode slurry. The negative electrode slurry is uniformly coated on the surface of a copper foil current collector with a thickness of 6 μm, dried at 100℃, and then cold-pressed and slit to obtain a negative electrode sheet.
[0083] Electrolyte: In a high-purity glove box filled with argon (moisture <0.1ppm, oxygen <0.1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a mass ratio of 3:5:2 as an organic solvent. Then, lithium hexafluorophosphate was slowly added to achieve a concentration of 1 mol / L. Finally, 1 wt% vinylene carbonate (VC) and 5 wt% fluoroethylene carbonate (FEC) were added as film-forming additives, accounting for 1 wt% of the total mass of the electrolyte (i.e., the total mass of organic solvent, lithium hexafluorophosphate, and additives). The mixture was stirred until homogeneous to obtain the electrolyte.
[0084] Diaphragm: A 12μm thick porous polyethylene (PE) membrane was selected as the separator.
[0085] Assemble the battery: The prepared composite positive electrode, separator, and negative electrode are stacked in sequence, with the separator isolating the positive and negative electrodes. Then, they are wound (or stacked) into a bare cell. The bare cell is placed in an aluminum-plastic film outer packaging and vacuum-baked at 85°C for 12 hours to thoroughly remove residual moisture from the electrodes and separator. Subsequently, the prepared electrolyte is injected into a glove box. After vacuum sealing, standing (setting the standing time to 24 hours to allow the electrolyte to fully wet the electrode pores and be fully absorbed by the HNBR network in the interface layer, causing swelling and in-situ gel formation), formation, and capacity testing, the finished soft-pack lithium-ion battery is obtained.
[0086] Examples 2-22 The preparation method is basically the same as that in Example 1, except that the content of each component in the coating, the parameters of the first polymer, the type of the second polymer, the type of solid electrolyte, the thickness of the interface layer or the type of additives are adjusted according to Table 1. Except for the differences listed in Table 1, the preparation of the positive electrode material layer, the preparation of the negative electrode sheet, the composition of the electrolyte, the selection of the separator, the assembly method, baking, liquid injection, standing, formation and capacity separation steps are the same as those in Example 1.
[0087] Comparative Examples 1-3 The preparation methods of Comparative Examples 1 to 3 are basically the same as those of Example 1, except that the interface layer setting method or interface layer composition is adjusted according to Table 1; except for the differences listed in Table 1, the other preparation steps and test conditions are the same as those of Example 1.
[0088] Table 1
[0089] In Table 1, the contents of chemical oxygen scavenger, solid electrolyte, polymer matrix, and additives are all calculated based on the total mass of the dry film of the interface layer; the mass ratio of the first polymer and the second polymer is calculated based on the mass of the first polymer and the second polymer in the polymer matrix.
[0090] Performance testing methods: 1) Room temperature cycling test: Under an environment of (25±2)℃, a 1C constant current charge-discharge cycle was performed at a preset voltage window of 2.5V-4.25V. The change trend of discharge capacity with the cycle was recorded to characterize the capacity retention and decay rate.
[0091] 2) Electrochemical impedance spectroscopy (EIS) test: After the cell has completed formation and the selected number of cycles, the cell is subjected to EIS testing (the test state of charge is 100% SOC) to obtain impedance spectra and track the changing trends of interface-related impedance parameters such as Rct, which are used to characterize the growth of interface impedance and ion transport status.
[0092] 3) Gas production assessment during high-temperature storage: The battery cells were charged to 100% SOC and stored at 55°C for 7 days. The gas generation and side reaction trends were evaluated by measuring the changes in cell thickness.
[0093] 4) Thermal abuse test: Under controlled conditions, a hot chamber temperature rise test was conducted, and the trends in temperature rise and the appearance of abnormal signs were recorded to help evaluate the inhibitory effect of the interface layer on the side reaction chain reaction. The temperature rise rate of the hot chamber was 2℃ / s, and the hot chamber test was conducted at 135℃. This test was only used for trend comparison and should not be used as the sole basis for an absolute safety conclusion.
[0094] Table 2
[0095] Based on the test data in Table 2, we can see that: When the oxygen scavenger content is high, the gas production and thermal safety performance of high-temperature storage will be improved. However, since the oxygen scavenger and its oxidation products may increase the interfacial ion transport resistance, the cycle performance and Rct will decrease slightly. When the interfacial layer thickness is small, the Rct is low, but the oxygen scavenging capacity is relatively insufficient, and the gas production is high. When the interfacial layer thickness is large, the oxygen scavenging capacity is enhanced, the gas production is reduced, but the Rct increases slightly.
[0096] Specifically, comparing Example 1 and Example 22 (without inorganic solid electrolyte), when an oxide solid electrolyte was added to the interface layer, the interfacial impedance (Rct) decreased from 21 mΩ to 8.5 mΩ, and the room temperature cycling retention rate increased from 78% to 90%. This strongly demonstrates that inorganic solid electrolyte fillers are key to constructing the interfacial ion permeation network and reducing polarization.
[0097] Further comparison of Examples 1, 19, and 20 reveals that the interface layer thickness affects the balance between oxygen capture capability and ion transport impedance. Example 19 uses a 0.5 μm interface layer, which is relatively thin, resulting in a shorter ion transport path and thus a relatively low Rct. However, due to the lower loading of oxygen scavenger and inorganic solid electrolyte per unit area, its buffering capacity against oxygen evolution at the cathode and side reactions is relatively weaker than in Example 1, leading to a relatively higher thickness expansion rate during high-temperature storage. Example 20 uses a 5 μm interface layer, which has a higher loading of functional components per unit area, resulting in better gas generation suppression. However, the increased interface layer thickness prolongs the lithium-ion cross-interface migration path and increases the tortuosity of transport within the coating, thus relatively increasing Rct and relatively decreasing cycle capacity retention. This demonstrates that the safety improvement effect of this application can be achieved with an interface layer thickness ranging from 0.5 μm to 5 μm, but a balance exists between oxygen capture capability, ion transport capability, and cycle stability at different thicknesses.
[0098] Comparing Example 1 and Comparative Example 3 (PVDF only, without HNBR), although both added a solid electrolyte, Comparative Example 3, lacking the first polymer swelling network, exhibited an interfacial impedance of 17 mΩ and a lower cycling capacity retention than Example 1. This result demonstrates that the liquid-containing gel network formed by the first polymer plays a crucial role in balancing oxygen scavenger fixation, interfacial wetting, and ion transport. Comparing Comparative Example 1 (blank) and Comparative Example 2 (without oxygen scavenger), the thickness expansion rate during high-temperature storage decreased from 12.5% to 10.9%. This shows that while coating with a ceramic + polymer layer without oxygen scavenging function can slightly reduce gas production by physically isolating the cathode and electrolyte, the cell still faces a serious risk of gas expansion. This indicates that simple physical shielding cannot effectively solve the oxidation decomposition problem caused by oxygen evolution in high-nickel cathodes.
[0099] Example 1, based on Comparative Example 2, introduced a chemical oxygen scavenger, reducing the gas production expansion rate to 3.5%. This significant performance improvement powerfully demonstrates that the active chemical scavenging mechanism employed in this invention is the decisive factor in suppressing interfacial side reactions in high-nickel systems and cutting off the gas production source, and its effect is far superior to traditional physical barrier methods.
[0100] Comparative Example 3 (without network A / PVDF only) showed good gas generation suppression (3.8%), but still failed the severe 135℃ hot box test (igniting after 40 minutes). Under relatively slow conditions such as high-temperature storage, the oxygen scavenger can still suppress gas generation to some extent; however, under rapid heating conditions in the hot box, the release of active oxygen and the rate of side reactions on the positive electrode side are significantly accelerated. If the interface layer lacks sufficient wetting and mass transfer channels, the contact efficiency between the oxygen scavenger, active oxygen, and electrolyte is limited, making it difficult to buffer the rapidly released active oxygen in a timely manner.
[0101] During slow, high-temperature storage, oxygen has sufficient time to slowly permeate into the dense PVDF layer and be captured, resulting in a low gas production rate. However, under the simulated thermal runaway conditions in the hot chamber, a large amount of reactive oxygen is released instantaneously at the positive electrode. Because Comparative Example 3 uses a dense, non-swellable PVDF substrate and lacks electrolyte wetting channels, the oxygen mass transfer rate is limited, preventing the oxygen scavenger from instantly contacting and consuming the explosively increasing oxygen.
[0102] Example 1 successfully passed the hot chamber test (without ignition), demonstrating that the liquid-containing gel channel constructed by the HNBR network not only facilitates ion transport but also provides an efficient mass transfer medium for the oxygen capture reaction, ensuring that the oxygen capture kinetic rate matches the thermal runaway reaction rate, thereby achieving true extreme safety protection.
[0103] In the description of this invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0104] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0105] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A composite positive electrode, characterized in that, include: Positive current collector; A positive electrode material layer is disposed on at least one side of the positive electrode current collector; An interface layer is disposed on the side of the positive electrode material layer away from the current collector, and includes a polymer matrix and an oxygen scavenger. The oxygen scavenger is dispersed in the polymer matrix, and the polymer matrix includes a first polymer that can absorb electrolyte and swell.
2. The composite positive electrode sheet according to claim 1, characterized in that, The oxygen scavenger is adsorbed onto the first polymer.
3. The composite positive electrode sheet according to claim 2, characterized in that, The first polymer has a strongly polar group, which includes at least one selected from cyano, carbonyl, ester, amide, etheroxy, hydroxy, carboxyl, sulfonyl, and phosphonate groups. The oxygen scavenger has a polar group, which includes at least one of sulfite, phosphite, hypophosphite, hydroxyl, silanol, carboxylate, metal-oxygen bond, and metal coordination site.
4. The composite positive electrode sheet according to claim 1, characterized in that, The interface layer also includes an inorganic solid electrolyte, which is dispersed in the polymer matrix.
5. The composite positive electrode sheet according to claim 4, characterized in that, At least one of the following conditions must be met: The oxygen scavenger includes at least one of a chemically active oxygen scavenger and a physically adsorbed oxygen scavenger, preferably the chemically active oxygen scavenger. The inorganic solid electrolyte includes at least one of oxide solid electrolyte, halide solid electrolyte, and sulfide solid electrolyte; The first polymer comprises hydrogenated nitrile butadiene rubber.
6. The composite positive electrode sheet according to claim 5, characterized in that, At least one of the following conditions must be met: The chemically active deoxidizing agent includes at least one of sulfite, phosphite, and hypophosphite; The physical adsorption type oxygen scavenger includes at least one of zeolite molecular sieve, metal-organic framework material, and porous silica. The oxide solid electrolyte includes at least one of garnet-type solid electrolyte, perovskite-type solid electrolyte, NASICON-type solid electrolyte, and LISICON-type solid electrolyte; The halide solid electrolyte includes Li3YCl6; The sulfide solid electrolyte includes a sulfide-germanium ore type solid electrolyte, preferably including at least one of Li6PS5X and LGPS type solid electrolytes, wherein X is selected from Cl, Br and I; The acrylonitrile content of the hydrogenated nitrile rubber is >30%; The degree of hydrogenation of the hydrogenated nitrile butadiene rubber is <98%, preferably 90% < the degree of hydrogenation of the hydrogenated nitrile butadiene rubber <98%.
7. The composite positive electrode sheet according to any one of claims 1 to 6, characterized in that, The polymer matrix further includes a second polymer, which does not swell in the electrolyte; The second polymer may comprise a matrix polymer or a reinforcing phase.
8. The composite positive electrode sheet according to claim 7, characterized in that, At least one of the following conditions must be met: The matrix polymer includes fluorinated polymers, preferably including at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluorochloroethylene copolymer, polytetrafluoroethylene, and ethylene-tetrafluoroethylene copolymer; The reinforcing phase is dispersed in the matrix polymer, or the reinforcing phase is composite with the matrix polymer; The shape of the reinforcing phase includes at least one of microparticles and fibers; The reinforcing phase includes at least one of polyimide and polyamide-imide; Based on the total mass of the second polymer, the mass percentage of the reinforcing phase is 1wt%-30wt%, preferably 5wt%-20wt%; The mass ratio of the first polymer to the second polymer is 20:80 to 80:20, preferably 30:70 to 70:
30.
9. The composite positive electrode sheet according to claim 4, characterized in that, At least one of the following conditions must be met: The thickness of the interface layer is 0.5μm to 5μm; Based on the total mass of the interface layer, the polymer matrix has a mass percentage content of 10-70 wt%, preferably 20-50 wt%. Based on the total mass of the interface layer, the oxygen scavenger has a mass percentage content of 5-35 wt%, preferably 10-25 wt%. Based on the total mass of the interface layer, the mass percentage of the inorganic solid electrolyte is 10-80 wt%, preferably 30-60 wt%.
10. The composite positive electrode sheet according to any one of claims 1 to 9, characterized in that, The interface layer further includes an auxiliary agent, and the auxiliary agent satisfies at least one of the following conditions: The additives include at least one of dispersants, rheology modifiers, and conductive agents; Based on the total mass of the interface layer, the mass percentage of the additive does not exceed 10 wt%.
11. The composite positive electrode sheet according to any one of claims 1 to 10, characterized in that, The cathode material layer includes a medium-high nickel ternary cathode material, wherein the percentage of nickel in the total molar amount of transition metal elements in the medium-high nickel ternary cathode material is not less than 60%.
12. A battery, characterized in that, The device includes a positive electrode, a negative electrode, a gel-state interface layer, and an electrolyte. The gel-state interface layer is disposed between adjacent positive and negative electrode sheets. The gel-state interface layer is formed by the interface layer absorbing the electrolyte and swelling. The interface layer is defined as described in any one of claims 1 to 11.
13. An electrical appliance, characterized in that, It includes the composite positive electrode sheet according to any one of claims 1 to 11 or the battery according to claim 12.